Efektivitas Minyak Ikan Lemuru Terproteksi Terhadap Populasi Mikrob Rumen dan Fermentasinya pada Kerbau dan Sapi (THE EFFECT OF PROTECTED LEMURU FISH OIL ON RUMEN MICROBES AND ITS FERMENTATION IN BUFFALOES AND CATTLE) - ., Yurleni; Priyanto, Rudy; Gurnadi, Eddy; Wiryawan, Komang Gede (Jurnal Veteriner; Vol 14 No 3 (2013), 2013)
The objective of this experiment was to examine the effect of protected lemuru fish oil on rumenmicrobes and its fermentation  in buffalo and cattle fattened in feedlot.  Six  male buffaloes and eight malecattle aged between 1,5-2 years old with initial live weight of 218,66±16,28 kg and 217,37±15,44 kg,respectively, were used in this study. They were fattened in feedlot using 35% forage and 65% concentratediet for 2,5 months. The protected lemuru fish oil was in the form of dried carboxylate salt mixture (DCM)and given in the form of concentrate mixture,  45 g DCM/kg concentrate. The feeding treatments includedPO (forage+concentrate) dan P1 (forage+concentrate+DCM). At the end of feeding trial, the animals wereslaughtered and the rumen liquor were collected to analyze rumen microbes and its fermentation.  Thedata were  analyzed using a completely randomized design with 2x2 factorial models, feeding trial (PO and P1) as the first factor  and  animals as second factor (buffaloes and cattle). The results showed that nointeraction was found between the two factors on  rumen pH, NH3 concentration, partial VFA, and rumenmicrobes. There were interaction effect of  diets treatment and animal species on total VFA. Total VFAconcentration in buffaloes  with DCM supplementation was significantly higher (P<0,05) than cattle  withor without DCM supplementation. DCM supplementation decreased rumen pH and increased total VFA.The buffaloes had significantly higher total VFA, proteolitic bacteria, and butiric acid,  but  had lowerrumen pH and protozoa population compared to those of cattle. It is concluded that DCM supplementationcan increase the effectivity of   protected fish oil concentration and proportion of VFA as well as rumenmicrobial population.
Keywords: fish oil, DCM, protection, cattle, buffalo